Handbook of environmental chemistry - Murphy, Clayton (NY Research Press, 2015)
Environmental chemistry is a rapidly expanding discipline of science. It integrates chemistry and environment in a manner which is most beneficial for humans. This book attempts to understand the multiple branches of environmental chemistry and how it can be useful in our lives. The various concepts that are constantly contributing towards advancing technologies and the evolution of this field are looked at in detail here.